Cyberbullying victimization during COVID-19: psychological effects and the legal measures - Zeti Zuryani Mohd Zakuan; Rizauddin Saian (International Journal of Public Health Science (IJPHS), 2022)
March 2020 has seen thousands of people across the globe have been infected with coronavirus disease 2019 (COVID-19). Apart from that, the pandemic has affected the learning of billions of students worldwide. As a result, educational institutions throughout the world have turned to online learning using online platforms. Online platforms not only cater to virtual learning, but the students will also have unrestricted access to their social media accounts and online games. Due to this situation, there has been an increase in violence and hate online, which includes bullying. The study reviewed articles to identify cyberbullying victimization during COVID-19. Articles published during COVID-19 pandemic from January 2020 to April 2021 were identified for review. The article search was conducted in April 2020 using the search engine on the National Centre for Biotechnology and Information (NCB) website and Google Scholar. Nineteen articles were chosen as being appropriate for the study's scope. The review highlights the presence and the psychological effects of cyberbullying during COVID-19. The current preventive measure in place is the legal measures. However, the legal measures are found not to be effective in combating cyberbullying.